An energy method for computing the use of fossil fuel energy (Nexo Revista Científica, 2021)
An energy method for computing the use of fossil fuel energy has been considered in the article. On the world market, the fuel price depends on supply and demand and involves no energy costs for fuel production. An energy analysis of economic activity was suggested by Charles Hall, an American scientist, who introduced a notion of Energy Returned on Energy Invested, as a ratio between returned and invested energy, into scientific discourse. No account has been taken of invested energy depreciation in this method. All losses are fully incorporated, when the ratio between beneficially used energy in all process flow chains from fuel deposit exploration to energy utilisation, and the considered amount of natural fuel primary energy is taken as the coefficient of beneficial primary energy use (CBPEU). When CBPEU is determined, allowance is made for all potential energy losses; the depreciation degree of energy, contained in the fuel, from its deposit to a consumer, is defined. When energy of renewable sources is utilised, a coefficient of renewable sources energy conversion, defined as the ratio between energy delivered by a power unit throughout the entire operation period, and invested energy taking into account CBPEU over the same period, will represent an objective criterion of power unit efficiency.